Cytomegalovirus infection in heart transplantation: A single center experience. Issue 4 (17th April 2018) - Echenique, Ignacio A.; Angarone, Michael P.; Rich, Jonathan D.; Anderson, Allen S.; Stosor, Valentina
Abstract: Background: Cytomegalovirus (CMV) infection remains a major complication after heart transplantation with varying prophylaxis strategies employed. We sought to determine the impact of valganciclovir (VGC) duration on the epidemiology of CMV infections after heart transplantation. Methods: We performed a prospective cohort study of CMV donor (D) or recipient (R) seropositive heart transplant recipients from 2005 to 2012 who completed VGC prophylaxis, ranging from 3 to 12 months according to serostatus and induction immunosuppression. Univariate and multivariate logistic regression was performed. Results: Among 159 heart transplant recipients during the study period, 130 (82%) were eligible for VGC prophylaxis. CMV D/R serostatus was as follows: 24% D+/R−, 30% D+/R+, and 29% D−/R+. 65% and 21% received basiliximab and thymoglobulin induction, respectively, followed by maintenance tacrolimus, mycophenolate mofetil, and prednisone. Twenty‐one (16%) recipients suffered CMV infection. There was no association with comorbidities including diabetes mellitus, chronic kidney disease, or mechanical assist devices, nor were there associations with rejection, treatments of rejection, or mortality. When VGC prophylaxis duration was stratified by ≤6 vs ≥12 months, time from heart transplantation to CMV infection was delayed (median 247 vs 452 days, P  = .002) but there was no difference in days from VGC discontinuation to onset of CMV infection (median 72 vs 83 days, P  = .31). CMV infection occurred most frequently within 6‐16 weeks of VGC cessation, and 95% of infections occurred during the 6 months post‐prophylaxis period. Conclusions: Relative to ≤6 months, ≥12 months of VGC did not reduce incidence of CMV infection and only delayed time to onset. 95% of CMV infection occurs within 6 months after cessation of VGC.